Result of Minimal Invasive Lumbar Discectomy with Arthroscopic-Tubular Retractor System (Chiang Rai System) - ติรางกูร เปรมชัย; บุญมาประเสริฐ ต่อพงษ์; เพิ่มเยาว์ จิราพร (Journal of Health Science of Thailand, 2020)
Nowadays, the minimal invasive spinal surgery technique was recognized from many centers for treated herniated nucleus pulposus (HNP) as it was not inferior to the standard technique and provided more benefit in less soft tissue injury, blood loss and shorter hospitalization. We had evaluated the outcome of local design Arthroscopic-tubular retractor system: Chiang Rai system. A retrospective study was performed at Chiang rai Prachanukroh Hospital in patients with herniated nucleus pulposus (HNP) during May 2016 to February 2019. All patients were operated for 1 level lumbar microdiscectomy with arthroscopic-tubular retractor system: Chiang Rai system by one surgeon. Numeric pain rating scale of back and leg pain, complications, length of stay, Oswestry low back disability index (ODI), and patient’s satisfaction using modified Macnab criteria were collected at the date of admission, 1st month, 6th month, 12th month and 24th month follow-ups. Thirty patients (16 males and 14 females) were included in the study. The average operating time was 134.5 minutes. Average blood loss was about 75.7 milliliters. Length of hospital stay was about 2.4 days. The mean NRS score of back pain/leg pain was improved from 6.7 to 1.5 and 8.4 to 0.9 respectively; and the mean ODI changed from 49.9 to 22.7 at 1stmonth, and gradually decrease along follow up study. Based on modified Macnab criteria, 86.6% patients had excellent to good results. Our designed “arthroscopic-tubular retractor system: Chiang Rai system” had quite satisfied results. Limitation of this study was small sample size, thus results of the use of this instrument would be collected continuously for more evaluation.